Perbedaan Tingkah Laku Makan Kambing Kacang Di TPA Desa Nanga Banda Dan Di Desa Nampar Tabang, Manggarai, Nusa Tenggara Timur - Achmadi, Puspita Cahya; Anggri, Yordianto; Maku, Nikolas Karan (Jurnal Ilmu dan Industri Peternakan, 2025)
Research on goat feeding behavior is used to see differences in several activities such as browsing and rumination activities of kambing kacang. This study used a sample of 20 bean goats with an average age of over 1 year. This research was conducted in two places, namely the Nanga Banda Landfill (TPA) and Nampar Tabang Village. The data that has been obtained will be analyzed using the t test. The results obtained that the difference in the behavior of peanut goats raised in the Nanga Banda Landfill and Nampar Tabang Village has a HI conclusion where the two groups have a tendency to differ in browsing and rumination eating behavior Thitung>Ttable. In browsing behavior 11.73> 2.10 and rumination 3.10> 2.10. There are several factors that can influence this, namely topography, availability of feed ingredients and weather.